Acetolactate Synthase-Inhibiting Gametocide Amidosulfuron Causes Chloroplast Destruction, Tissue Autophagy, and Elevation of Ethylene Release in Rapeseed - Liu, Xi-Qiong; Yu, Cheng-Yu; Dong, Jun-Gang; Hu, Sheng-Wu; Xu, Ai-Xia (Frontiers in Plant Science, 2017)
Background: Acetolactate synthase (ALS)-inhibiting herbicides amidosulfuron (Hoestar) is an efficient gametocide that can induce male sterility in rapeseed (Brassica napus L.). We conducted an integrated study of cytological, transcriptomic, and physiological analysis to decipher the gametocidal effect of amidosulfuron. Results: In the first several days after exposure to amidosulfuron at a gametocidal dose of ca. 1 μg per plant, the plants showed the earliest symptoms including short retard of raceme elongation, slight chlorosis on leaf, and decrease of photosynthesis rate. Chloroplasts in leaf and anther epidermis, and tapetal plastids were deformed. Both tapetal cell and uni-nucleate microspore showed autophagic vacuoles and degenerated quickly. The amidosulfuron treatment caused reduction of photosynthetic rate and the contents of leaf chlorophyll, soluble sugar and pyruvate, as well as content alteration of several free amino acids in the treated plants. A comparison of transcriptomic profiling data of the young flower buds of the treated plants with the control identified 142 up-regulated and 201 down-regulated differential expression transcripts with functional annotations. Down-regulation of several interesting genes encoding PAIR1, SDS, PPD2, HFM1, CSTF77, A6, ALA6, UGE1, FLA20, A9, bHLH91 and putative cell wall protein LOC106368794, and up-regulation of autophagy-related protein ATG8A indicated functional abnormalities about cell cycle, cell wall formation, chloroplast structure, and tissue autophagy. Ethylene-responsive transcription factor RAP2-11-like was up-regulated in the flower buds and ethylene release rate was also elevated. The transcriptional regulation in the amidosulfuron-treated plants was in line with the cytological and physiological changes. Conclusions: The results suggested that metabolic decrease related to photosynthesis and energy supply are associated with male sterility induced by amidosulfuron. The results provide insights into the molecular mechanisms of gametocide-induced male sterility and expand the knowledge on the transcriptomic complexity of the plants exposure to sulfonylurea herbicide.